2022
DOI: 10.1007/s11042-022-13373-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of victory in Esports - StarCraft II

Abstract: Esports offer a unique opportunity to conduct human performance studies, as they use modern hardware and software as an operation platform. Insights on gameplay and underlying processes may push the development of new and optimal practice methods. The aim of this study was to investigate performance indicators from in-game data to predict the outcome of the matches in StarCraft II: Legacy of The Void.Data from 6509 games (game records) provided by 5 players at the level of Master or GrandMaster were used. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Player metrics have also been used to predict the probability of a team winning a match in other eSport genres. For example, statistical models developed in previous research have indicated that the team win probability was connected with the distance to the objective in a first-person shooter (Xenopoulos et al, 2020), the distance of team members across a multiplayer online battle arena (MOBA) map (Rioult et al, 2014), and resources collected during the real-time strategy game, StarCraft II (Białecki et al, 2022). The subset of associations observed with the location of team members suggests a similar connection may be observed with collective metrics and team dynamics.…”
Section: Collective Behaviors In Team-based Esportsmentioning
confidence: 92%
“…Player metrics have also been used to predict the probability of a team winning a match in other eSport genres. For example, statistical models developed in previous research have indicated that the team win probability was connected with the distance to the objective in a first-person shooter (Xenopoulos et al, 2020), the distance of team members across a multiplayer online battle arena (MOBA) map (Rioult et al, 2014), and resources collected during the real-time strategy game, StarCraft II (Białecki et al, 2022). The subset of associations observed with the location of team members suggests a similar connection may be observed with collective metrics and team dynamics.…”
Section: Collective Behaviors In Team-based Esportsmentioning
confidence: 92%
“…In Poland, several psychological, sociological, sports and scientific-technical university research teams have already dealt with some issues of esports [9,15,68,[71][72][73][74], and virtualization as well as methods of formal measurement evaluation. The world of esports is open by nature, so access to research is easy.…”
Section: Virtualization and Ai Processes In Esportsmentioning
confidence: 99%
“…Custom game - Players join the lobby (game room), where all game settings are set and the readiness to play is verified by both players - this mode is used in tournament games. Immediately after the start of the game, players have access to one main structure, which allows for further development and production of units.” 22 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Immediately after the start of the game, players have access to one main structure, which allows for further development and production of units. " 22 .…”
mentioning
confidence: 99%